2000
DOI: 10.1002/(sici)1097-0223(200004)20:4<307::aid-pd797>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

A tobacco-specific carcinogen in the fetus

Abstract: A tobacco-specific carcinogen, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL), and its metabolite, 4-[(methylnitrosamino)-1-(3-pyridyl)but-1-yl]beta-O-D-glucosiduronic+ ++ acid (NNAL-Gluc), have been found in the urine of newborns whose mothers smoked during pregnancy. We set out to determine whether this carcinogen is present in the fetus in early pregnancy. Cell-free amniotic fluid (AF) was obtained through routine amniocentesis for prenatal genetic studies from groups of smokers and non-smokers. NNAL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Of these, N-nitroso compounds are the most likely candidate transplacental liver carcinogens (Anderson et al, 1989;Correa et al, 1990;Beebe et al, 1993;Schuller et al, 1993Schuller et al, , 1994Hecht, 1998). These compounds can cross the human placenta, and their metabolites have been found both in the urine and bound to the fetal haemoglobin of newborns whose mothers smoked cigarettes (Coghlin et al, 1991;Lackmann et al, 1999) and in the fetus in early pregnancy (Milunsky et al, 2000). Cord blood T lymphocytes from newborns has revealed an increased level of mutations (deletions in infants of mothers who smoked (Finette et al, 1997)).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, N-nitroso compounds are the most likely candidate transplacental liver carcinogens (Anderson et al, 1989;Correa et al, 1990;Beebe et al, 1993;Schuller et al, 1993Schuller et al, , 1994Hecht, 1998). These compounds can cross the human placenta, and their metabolites have been found both in the urine and bound to the fetal haemoglobin of newborns whose mothers smoked cigarettes (Coghlin et al, 1991;Lackmann et al, 1999) and in the fetus in early pregnancy (Milunsky et al, 2000). Cord blood T lymphocytes from newborns has revealed an increased level of mutations (deletions in infants of mothers who smoked (Finette et al, 1997)).…”
Section: Discussionmentioning
confidence: 99%
“…30 In addition, mutagenic chemicals from maternal smoking cross the placenta enhancing the plausibility of an effect of parental smoking on pediatric leukemia risk. 31 Our analysis showed a significant association between paternal smoking and hyperdiploid leukemia, in the inverse direction, when compared to other leukemia subtypes (see Results). Because parental smoking was not significantly associated with RAS mutation-positive leukemia overall (Table 1), this suggests that another molecular subtype of leukemia may be positively associated with paternal smoking.…”
Section: 23mentioning
confidence: 99%
“…Further, tobacco smoke contains 40 known carcinogens, which permeate the placenta and are passed to the fetus (Florek et al, 2011;Milunsky, Carmella, Ye, & Hecht, 2000). For example, one of the N-nitrosamines in tobacco smoke, nicotine-derived nitrosamine ketone (NNK), is a cause of lung cancer.…”
mentioning
confidence: 99%
“…For example, one of the N-nitrosamines in tobacco smoke, nicotine-derived nitrosamine ketone (NNK), is a cause of lung cancer. NNAL (4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol), a metabolite of NNK, has been found at elevated levels in newborns of mothers who smoke and also in newborns of nonsmoking mothers exposed to SHS (Milunsky et al, 2000). Florek et al (2011) reported that more than 50% of infants with nonsmoking mothers who reported exposure to SHS during pregnancy had detectable levels of NNAL in their urine at birth.…”
mentioning
confidence: 99%